2003
DOI: 10.1159/000070864
|View full text |Cite
|
Sign up to set email alerts
|

Death with Functioning Graft in Living Donor Kidney Transplantation: Analysis of Risk Factors

Abstract: Background: Death with a functioning graft (DWF) has been reported as a major cause of graft loss after renal transplantation. It has been reported to occur in 9–30%. Methods: From March 1976 to January 2002, a total of 1,400 living donor renal transplants were performed in our center. Out of 257 reported deaths among our patients, 131 recipients died with functioning grafts after a mean period of 53.4 ± 53.2 months. Results: DWF patients account for 27% of all graft losses in our series. The mean age was 34.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
1
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
1
15
1
12
Order By: Relevance
“…13,14 The main causes of death included cardiac problems, malignancy, and infection, and causes of graft failure included recurrent disease and chronic rejection. 15,16 In a retrospective review of 4483 adult primary liver transplant recipients, major causes of death were malignancy (30.6%), multisystem failure (10%), infection (9.8%), graft failure (9.8%), and CVD (8.7%). 17 El-Agroudy et al 15 found the main causes of death in kidney allograft recipients were infections (35.6%), CVD (17.6%), liver disease (11.4%), and malignancy (6.1%).…”
Section: Modifiable Risk Factors For Graft Loss Posttransplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 The main causes of death included cardiac problems, malignancy, and infection, and causes of graft failure included recurrent disease and chronic rejection. 15,16 In a retrospective review of 4483 adult primary liver transplant recipients, major causes of death were malignancy (30.6%), multisystem failure (10%), infection (9.8%), graft failure (9.8%), and CVD (8.7%). 17 El-Agroudy et al 15 found the main causes of death in kidney allograft recipients were infections (35.6%), CVD (17.6%), liver disease (11.4%), and malignancy (6.1%).…”
Section: Modifiable Risk Factors For Graft Loss Posttransplantationmentioning
confidence: 99%
“…15,16 In a retrospective review of 4483 adult primary liver transplant recipients, major causes of death were malignancy (30.6%), multisystem failure (10%), infection (9.8%), graft failure (9.8%), and CVD (8.7%). 17 El-Agroudy et al 15 found the main causes of death in kidney allograft recipients were infections (35.6%), CVD (17.6%), liver disease (11.4%), and malignancy (6.1%). Of nearly 1600 kidney recipients in Japan, Shimmura et al 16 found the main causes of death with a functioning graft were infection (24%), stroke (17%), CVD (16%), malignancy (15%), and liver failure (12%).…”
Section: Modifiable Risk Factors For Graft Loss Posttransplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…l trasplante renal (TxR) ofrece expectativas de sobrevida y calidad de vida mejores que la permanencia en diálisis crónica (DC) a los pacientes con insufi ciencia renal crónica (IRC) 1,2 . Actualmente, la sobrevida de los sujetos que reciben un TxR es del orden de 95% al año y de 90% a los 3 a 5 años de la intervención 3 .…”
unclassified
“…La nefropatía crónica del injerto y la muerte con riñón funcionante (MCRF) son las principales causas de pérdida de los TxR después del primer año de la intervención, resultando en una pérdida anual de 3-5% de los injertos [1][2][3][4][5][6][7] . Si bien la mortalidad de los pacientes trasplantados es inferior a la de los sujetos que permanecen en DC, su sobrevida es inferior a la de controles pareados por edad en la población general [1][2][3][4][8][9] . La mortalidad es 14,7 veces mayor durante el primer año del TxR y 4,4 veces mayor después de este período 1,10 .…”
unclassified